The Relationship of Knowledge with Mother's Readiness to Give Exclusive Breastfeeding - Lisna Liani; Linda Telaumbanua; Rupdi Lumban Siantar (Genius Midwifery Journal, 2023)
Introduction: Preparation for breastfeeding during pregnancy is very important, mothers who prepare early will be better prepared to breastfeed their babies. A mother's readiness to give exclusive breastfeeding is influenced by several factors, one of which is knowledge. Exclusive breastfeeding coverage at Mustika Jaya Health Center in 2021 is 215 (44.51%) of 483 babies. The percentage of exclusive breastfeeding coverage has not reached the expected target Aims: The purpose of the study was to determine the relationship between the knowledge of third-trimester pregnant women about lactation management and the readiness of mothers to give exclusive breastfeeding at the Mustika Jaya Health Center. Methods: The research design is a correlational study with a cross-sectional approach. The population was all third-trimester pregnant women at the Mustika Jaya Health Center on 24 September 2022 and 15 October 2022 as many as 125 people and the sample was 95 people with a simple random sampling technique. The data was collected using a questionnaire and the data analysis included frequency distribution and chi-square test. Results: Most of the third-trimester pregnant women have sufficient knowledge (37.9%) and have the readiness to give exclusive breastfeeding (65.3%). There is a relationship between the knowledge of third-trimester pregnant women about lactation management and with mother's readiness to give exclusive breastfeeding at Mustika Jaya Health Center with a value = 0.000. Conclusion: The conclusionÂ of this research is the existence of a relationship between the knowledge of third-trimester pregnant women about lactation management and with mother's readiness to give exclusive breastfeeding, it is necessary for health workers to provide counseling about lactation management on an ongoing basis to pregnant women.